PENDAMPINGAN PENINGKATAN OPTIMISASI CITRA MRCP DENGAN PENGGUNAAN TEH OOLONG DAN SUSU SOYA HERBAL SEBAGAI ALTERNATIF MEDIA KONTRAS NEGATIF ORAL DI RS KANKER KEN SARAS UNGARAN KABUPATEN SEMARANG - Fatimah Fatimah; Sugiyanto Sugiyanto; Gatot Murti Wibowo (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2016)
High intensities of gastrointestinal tract may interfere to image quality of pancreatobilliary system that affects MRCP image degradation. The method of implementation of community service activities are divided into two activities : dissemination of material about improving the image optimization deployment training MRCP and use of oolong tea and herbal soy milk as an alternative oral negative contrast agent. Frameworks consist of input, process and output. Input as a potential target group's knowledge on the operation modalities of MRI and MRCP examination procedures. The process is in the form of training activities and the implementation of the use of oolong tea and herbal soy milk as an alternative to oral negative contrast agent on MRCP examination in hopes of generating output in the form of an increase in MRCP image optimization. Framework of solving problems through training implemented in the form of learning and mentoring using oolong tea and herbal soy milk as an alternative oral negative contrast agent MRCP, can produce contrast effect and image effect on the image enhancement MRCP optimization.